Factors affecting sexual function in menopause: A review article - Soheila Nazarpour; Masoumeh Simbar; Fahimeh Ramezani Tehrani (Elsevier, 2016)
This study aimed to systematically review the articles on factors affecting sexual function during menopause. Searching articles indexed in Pubmed, Science Direct, Iranmedex, EMBASE, Scopus, and Scientific Information Database databases, a total number of 42 studies published between 2003 and 2013 were selected. Age, estrogen deficiency, type of menopause, chronic medical problems, partner's sex problems, severity of menopause symptoms, dystocia history, and health status were the physical factors influencing sexual function of menopausal women. There were conflicting results regarding the amount of androgens, hormonal therapy, exercise/physical activity, and obstetric history. In the mental-emotional area, all studies confirmed the impact of depression and anxiety. Social factors, including smoking, alcohol consumption, the quality of relationship with husband, partner's loyalty, sexual knowledge, access to health care, a history of divorce or the death of a husband, living apart from a spouse, and a negative understanding of women's health were found to affect sexual function; however, there were conflicting results regarding the effects of education, occupation, socioeconomic status, marital duration, and frequency of sexual intercourse.